Ethyl 4-[3-(2-methylbenzoyl)thioureido]benzoate - Saeed, Aamer (International Union of Crystallography, 2009)
The molecular conformation of the title compound, C(18)H(18)N(2)O(3)S, is stabilized by an intramolecular N—H⋯O hydrogen bond. The crystal packing shows centrosymmetric dimers connected by N—H⋯S hydrogen bonds. The terminal ethoxy substituents are statistically disordered [occupancy ratio 0.527 (5):0.473 (5)].